Imidazole additives in 2D halide perovskites: impacts of –CN versus –CH3 substituents reveal the mediation of crystal growth by phase buffering. Issue 8 (22nd June 2022) - Yu, Shuang; Meng, Jie; Pan, Qinying; Zhao, Qian; Pullerits, Tõnu; Yang, Yingguo; Zheng, Kaibo; Liang, Ziqi
Abstract : A cyano-based DCI additive induces phase-buffering during the crystallization growth process of 2D halide perovskites, which effectively suppresses interphase strain, enhances lattice orientation and reduces trap-state density, delivering an outstanding and stable efficiency of ∼17.0% ( n = 4). Abstract : The unique sandwich structure and favorable crystallization kinetics have endowed two-dimensional (2D) halide perovskites with excellent ambient stability and facile film formation compared to those of their three-dimensional counterparts. However, the heterogeneous crystallization of multiple n -value phases during solution-casting of 2D perovskite thin films results in random and disordered crystalline alignment in conjunction with numerous lattice defects, all of which ultimately impair the device performance. Herein we demonstrate that highly ordered lattice arrangements in 2D lead halide perovskites, exemplified as a paradigm phenylethylamine (PEA) spacer, can be achieved using the 4, 5-dicyanoimidazole (DCI) additive without any post-treatment. Electrostatic potential distribution mapping and X-ray photoelectron spectroscopy collectively confirm the Lewis acid–base interaction between –CN − units in DCI and Pb 2+, which is conducive to homogeneous nucleation during perovskite crystallization. A sequence of in situ grazing-incident wide-angle X-ray scattering and high-resolution transmission electron microscopy characterization unravel the epitaxial growth of multi-phases that gradually buffer the internal lattice strain and consequently regulate the lattice orientation, which markedly leads to a reduction of trap density and a prolongation of carrier lifetime. The resulting planar solar cells based on 2D PEA2 MA3 Pb4 I13 ( n = 4) deliver an outstanding efficiency of ∼17.0% along with excellent operational stability.